Low-temperature sintering and enhanced stability of fluorine-modified BaZr0.8Y0.2O3-δ synthesised by a sol-gel alkoxide route. Issue 1 (January 2023) - Triviño-Peláez, Ángel; Mosa, Jadra; Pérez-Coll, Domingo; Aparicio, Mario; Mather, Glenn C.
Abstract: Sol-gel synthesis using alkoxides is employed to obtain fluorine-modified BaZr0.8 Y0.2 O3-δ nanopowders with Ba excess at 750 °C. Possible effects of F loss at high temperature were limited on densifying at the low temperature of 1200 °C for 4 h on addition of ZnO as sintering agent. The presence of F in sintered samples was confirmed by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry. XPS and Raman spectroscopy indicated that F doping of BZY inhibits carbonate formation. Conductivity measurements for prolonged periods in wet H2 -containing and CO2 -containing atmospheres at 500 °C also demonstrated chemical stability. The temperature dependence of the electrical conductivity of sintered samples in wet and dry N2 and O2 indicates that the grain-boundary dominates the electrical behaviour to 500 °C, above which the bulk process dominates. Ionic conduction is prevalent at low temperature, with a transition to a mixed ionic-electronic conducting behaviour at 450 °C.